IgG4 Inflammatory Pseudotumor of the Kidney - Ahmed N. Alkhasawneh; Robert W. Allan (Case Reports in Urology)
Hyper-IgG4 disease is a rare systemic disorder that usually affects middle age males. It is characterized by elevated serum IgG4 levels and infiltration of organs by IgG4 positive plasma cells associated with fibrosis. Patients usually present with mass or masses in the involved organ that mimic neoplasia. While initially described in the pancreas, IgG4-related inflammatory tumors have been now described in many organs. We describe an unusual case of an IgG4-related pseudotumor of the kidney.